Integrated concurrent programmable logic controller (PLC) based IR 4.0 training kit / Firdaus Sukarman ... [et al.] - Sukarman, Firdaus; Mat Shah, Muhammad Amir; Mazni, Mazleenda; Abdul Malik, Norjasween; Mohd Hamami, Mohd Ghazali (2020)
Programmable Logic Controller (PLC) is an industry standard equipment for integrated automation and vastly used in automotive, manufacturing and heavy industries. Reliable, robust and flexible to industries' environment make it the best solution for the current industrial control applications and monitoring of the robots and equipment in the plant. However, since it is an advanced application in industry, students have problems to understand the concept and see the whole objective why a certain process and correct sequence is required in the designated industry's system. Thus, the integrated system that includes Programmable Logic Control hardware, physical input output modules, and also visualization environment is developed as a training kit to improve the hands-on skills and holistic understanding of the system as whole. This combination of physical and software system brings new experience to students in learning ecosystem since they can operate using the input modules in laboratory, see the output feedback in real time and monitoring the whole process in visualization software.